Etika Komunikasi Dalam Penggunaan Trash-Talking Pemain Mobile Legends Pada Komunitas Evosfams - Rafly, Muhamad; Erland Hamzah, Radja; Kardi Wiyati, Eni (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study aims to understand the reasons why Mobile Legends players in the EVOS Fams community use trash-talking in their communication interactions and to determine whether trash talking in the EVOS Fams community is considered a common and acceptable practice within the context of ethical communication. The research method used is descriptive qualitative. Data collection techniques include in-depth interviews and documentation involving three members of the EVOS Fams community. Data validity is ensured through source triangulation and analyzed using data reduction, data presentation, and conclusion drawing. The research findings indicate that Mobile Legends players in the EVOS Fams community use trash-talking for strategic, psychological, and social reasons. Strategically, it aims to intimidate opponents. Psychologically, it serves as an emotional outlet or a defense mechanism. Socially, it functions as a way to gain attention, build relationships, and enhance interactions within the community, with team support reinforcing this habit. Trash-talking in the EVOS Fams community is acceptable as long as it remains within reasonable limits, does not involve personal attacks, and respects opponents. As a competitive strategy and form of entertainment, its use should align with community norms. However, excessive use involving harsh words or insults can create a negative environment. Therefore, ethical communication in trash-talking should uphold respect and politeness to ensure positive interactions.